2021
DOI: 10.1177/15330338211039109
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA HOXA-AS2 Promotes Oral Squamous Cell Proliferation, Migration, and Invasion via Upregulating EZH2 as an Oncogene

Abstract: Oral squamous cell carcinoma (OSCC) is one of the most common types of cancer worldwide. Accumulating evidence has shown that long noncoding RNAs (lncRNAs) serve important roles in the development of OSCC. The purpose of this study was to investigate the biological function and underlying regulatory mechanism of lncRNA homeobox A cluster antisense RNA2 (HOXA-AS2) in OSCC. RT-qPCR was performed to analyze the HOXA-AS2 expressions in human immortalized oral epithelial cell (HIOEC) line, human OSCC cell lines, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…As an oncogene, lncRNA HOXA-AS2 exhibits abnormally high expression in a wide array of solid and hematological malignancies, such as acute myeloid leukemia (AML) (10), gallbladder cancer (11) and glioma (12), promoting the progression of these cancer types. The mechanisms by which lncRNA HOXA-AS2 inhibits apoptosis and stimulates proliferation have been the most extensively studied (13)(14)(15), indicating that lncRNA HOXA-AS2 not only affects the proliferation, invasion and migration of cancer cells but is also closely related to patient prognosis. For instance, the upregulation of lncRNA HOXA-AS2 in AML (10) demonstrates its oncogenic role by interacting with the epigenetic inhibitor Enhancer of zeste homolog 2 (EZH2), subsequently repressing the expression of Large Tumor Suppressor 2 (LATS2).…”
Section: Lncrna Hoxa-as2 Is a Prognostic And Clinicopathological Pred...mentioning
confidence: 99%
“…As an oncogene, lncRNA HOXA-AS2 exhibits abnormally high expression in a wide array of solid and hematological malignancies, such as acute myeloid leukemia (AML) (10), gallbladder cancer (11) and glioma (12), promoting the progression of these cancer types. The mechanisms by which lncRNA HOXA-AS2 inhibits apoptosis and stimulates proliferation have been the most extensively studied (13)(14)(15), indicating that lncRNA HOXA-AS2 not only affects the proliferation, invasion and migration of cancer cells but is also closely related to patient prognosis. For instance, the upregulation of lncRNA HOXA-AS2 in AML (10) demonstrates its oncogenic role by interacting with the epigenetic inhibitor Enhancer of zeste homolog 2 (EZH2), subsequently repressing the expression of Large Tumor Suppressor 2 (LATS2).…”
Section: Lncrna Hoxa-as2 Is a Prognostic And Clinicopathological Pred...mentioning
confidence: 99%
“…Li et al demonstrated that HOXA-AS2 is highly expressed in CRC tissues compared to normal tissues, and its expression can serve as a predictor of poor prognosis in CRC patients [ 151 ]. The association between HOXA-AS2 and EZH2 has also been confirmed in PC [ 152 ], OSCC [ 153 ], acute myeloid leukemia (AML) [ 154 ], and glioma [ 155 ]. Furthermore, the downregulation of HOXA-AS2 induces cell apoptosis, arrests the cell cycle in the G1 phase, and inhibits metastasis and invasion in GBC [ 156 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies indicated that the expression of HOXA-AS2 was strikingly upregulated in many types of cancers, such as in non-small cell lung cancer, bladder cancer and pancreatic cancer [ 12 – 15 ]. In addition, it was found that HOXA-AS2 promoted OSCC progression by upregulating EZH2 [ 16 ] or inhibiting miR-567 expression [ 17 ]. But, a better understanding of the roles of HOXA-AS2 in OSCC remains to be further studied.…”
Section: Introductionmentioning
confidence: 99%